Automatically Welded Tubular X‐Joints for Jacket Substructures: Prediction of the Technical Fatigue Crack Location. Issue 3 (16th September 2019) - Schaumann, Peter; Schürmann, Karsten; Pittner, Andreas; Rethmeier, Michael
ABSTRACT: To increase the competitiveness of jacket substructures compared to monopiles a changeover from an individual towards a serial jacket production based on automated manufactured tubular joints combined with standardized pipes has to be achieved. Therefore, this paper addresses fatigue tests of automatically welded tubular X‐joints focusing on the location of the technical fatigue crack. The detected location of the technical crack is compared to numerical investigations predicting the most fatigue prone notch considering the structural stress approach as well as the notch stress approach. Besides, the welding process of the automated manufactured tubular X‐joints is presented.